Representaciones de pueblos originarios en la historieta chilena contemporánea. Un catastro de publicaciones entre 1998-2023 (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
This article examines the representation of indigenous peoples in Chilean comics published between 1998 and 2023, analyzing 57 identified titles. The study reveals a significant increase in the production and diversification of these narratives, coinciding with sociopolitical changes in Chile that have reconfigured the relationships between the state and indigenous peoples. A predominance of representations of the Mapuche people (59.6%) is observed, followed by the Selk'nam (19.3%) and Rapa Nui (8.8%). The analysis covers format, temporality, target audience, and genre, evidencing a trend toward more complex and multidimensional narratives. This new scenario of comic production is critically discussed as a space for cultural negotiation, identity construction, and the articulation of alternative narratives.